2022
DOI: 10.1101/2022.07.22.22277884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the genetic architecture of cam morphology, and its relationship with hip osteoarthritis, using alpha angle as a proxy measure

Abstract: Objectives To examine the genetic architecture of cam morphology, using alpha angle (AA) as a proxy measure, we conducted an AA genome wide association study (GWAS), followed by Mendelian randomisation (MR) to evaluate its causal relationship with hip osteoarthritis (HOA). Methods: Observational analyses examined associations between AA derived from hip DXA scans in UK Biobank (UKB), and radiographic HOA (rHOA) and subsequent total hip replacement (THR). Afterwards, an AA GWAS meta-analysis was performed (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…An alternative explanation is that the femoral neck is widened as part of, or in parallel to the onset of HOA rather than the widened femoral neck causing HOA. Recent evidence from studies using SSM suggests a wider femoral neck is associated with more severe HOA and separately a genetic study suggested that a genetic predisposition to HOA led to cam-like changes at the femoral head ( 11 , 26 , 27 ). Both these studies suggest that hip shape is associated with but might not be a cause of HOA which has treatment implications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation is that the femoral neck is widened as part of, or in parallel to the onset of HOA rather than the widened femoral neck causing HOA. Recent evidence from studies using SSM suggests a wider femoral neck is associated with more severe HOA and separately a genetic study suggested that a genetic predisposition to HOA led to cam-like changes at the femoral head ( 11 , 26 , 27 ). Both these studies suggest that hip shape is associated with but might not be a cause of HOA which has treatment implications.…”
Section: Resultsmentioning
confidence: 99%
“…The strengths of this study include its large sample size obtained through novel automated measures which have facilitated the description of DXA-derived hip geometry in UK Biobank, including the derivation of DFH which is not provided by existing HSA software. A sample size of this magnitude paves the way for future use of genetic epidemiological methods, which can add further understanding of aetiology of hip shape and its role in the pathogenesis of HOA ( 26 , 35 ). In addition, this study showed how hip geometric measures are longitudinally associated with THR justifying further work to understand whether these measures could be combined with measures of DXA-derived radiographic HOA to better understand THR risk.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation is that the femoral neck is widened as part of, or in parallel to the onset of HOA rather than the widened femoral neck causing HOA. Recent evidence from studies using SSM suggests a wider femoral neck is associated with more severe HOA and separately a genetic study suggested that a genetic predisposition to HOA led to cam-like changes at the femoral head (11,26,27). Both these Hip geometry and its associations with hip osteoarthritis studies suggest that hip shape is associated with but might not be a cause of HOA which has treatment implications.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study include its large sample size obtained through novel automated measures which have facilitated the description of DXA-derived hip geometry in UKB, including the derivation of DFH which is not provided by existing HSA software. A sample Hip geometry and its associations with hip osteoarthritis size of this magnitude paves the way for future use of genetic epidemiological methods, which can add further understanding of aetiology of hip shape and its role in the pathogenesis of HOA (26,35). In addition, the use of DXA scans which require lower radiation exposure than Xrays makes them more desirable for screening (10,36).…”
Section: Discussionmentioning
confidence: 99%